Clinical Encounters in Sexuality: Psychoanalytic Practice and Queer Theory - Watson, Eve; Giffney, Noreen; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2020)
Clinical Encounters in Sexuality makes an intervention into the fields of clinical psychoanalysis and sexuality studies, in an effort to think about a range of issues relating to sexuality from a clinical psychoanalytic perspective. The editors have chosen queer theory as an interlocutor for the clinical contributors, because it is at the forefront of theoretical considerations of sexuality, as well as being both reliant upon and suspicious of psychoanalysis as a clinical practice and discourse. The book brings together a number of psychoanalytic schools of thought and clinical approaches, which are sometimes at odds with one another and thus tend not to engage in dialogue about divisive theoretical concepts and matters of clinical technique. The volume also stages, for the first time, a sustained clinical psychoanalytic engagement with queer theory. The central questions we present to readers to think about are: What are the discourses of sexuality underpinning psychoanalysis, and how do they impact on clinical practice? In what ways does sexuality get played out for, and between, the psychoanalytic practitioner and the patient? How do social, cultural and historical attitudes towards sexuality impact on the transference and countertransference, consciously and unconsciously? Why is sexuality so prone to reification?
Introduction. Clinical encounters in sexuality : psychoanalytic practice and queer theory / Noreen Giffney -- Identity. Precarious sexualities : queer challenges to psychoanalytic and social identity categorization / Alice Kuzniar -- Desire. Missing something? Queer desire / Lara Farina -- Pleasure. Jouissance : the gash of bliss / Kathryn Bond Stockton -- Perversion. Perversion and the problem of fluidity and fixity / Lisa Downing -- Ethics. Out of line, on hold : D.W. Winnicott's queer sensibilities / Michael Snediker -- Discourse. Discourse and the history of sexuality / Will Stockton -- On not thinking straight : comments on a conceptual marriage / R.D. Hinshelwood -- Queer as a new shelter from castration / Abe Geldhof and Paul Verhaeghe -- The redress of psychoanalysis / Ann Murphy -- Queer directions from Lacan / Ian Parker -- Queer theory meets Jung / Claudette Kulkarni -- Queer troubles for psychoanalysis / Carol Owens -- Clinique / Aranye Fradenburg -- From tragic fall to programmatic blueprint : "Behold this is Oedipus..." / Olga Cox Cameron -- Enigmatic Sexuality. Katrine Zeuthen and Judy Gammelgaard -- The transforming nexus : psychoanalysis, social theory and queer childhood / Ken Corbett -- Clinical encounters : the queer new times / Rob Weatherill -- Undoing psychoanalysis : towards a clinical and conceptual metistopia / Dany Nobus -- "You make me feel like a natural woman:" thoughts on a case of transsexual identity formation and queer theory / Ami Kaplan -- Sexual difference : from symptom to sinthome / Patricia Gherovici -- A plague on both your houses / Stephen Frosh -- Something amiss / Jacqueline Rose -- Taking shelter from queer / Tim Dean -- Courageous drawings of vigilant ambiguities / Noreen O'Connor -- Understanding homophobia / Mark J. Blechner -- Transgender, queer theory, and psychoanalysis / Susan Stryker -- The psychoanalysis that dare not speak its name / Ona Nierenberg -- On the not-meanings of Karla Black's There can be no arguments / Medb Ruane -- Afterword. Reflections on the encounters between psychoanalysis and queer theory / Eve Watson.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Psychoanalysis -- Philosophy; Sex (Psychology); Queer theory; Electronic books